Improving Running Economy by Transitioning to Minimalist Footwear: A Randomised Controlled Trial. Issue 12 (December 2018) - Lindlein, K.; Zech, A.; Zoch, A.; Braumann, K.-M.; Hollander, K.
Abstract: Objectives: Ongoing debates about benefits and risks of barefoot- and minimally-shod running have, to date, revealed no conclusive findings for long-term effects on physical performance. The purpose of this study was to examine the effects of an 8-week transition to minimalist footwear (MFW) on running economy (RE). Design: Randomised controlled trial. Methods: Thirty-two male, habitually-shod runners were assigned randomly to an 8-week training intervention either in minimalist (=intervention group) or conventional running shoes (=control group). The intervention consisted of a gradual increase in use of the new footwear by 5% of the individual weekly distance. Before and after the intervention, a VO2 max test was followed by a submaximal RE test at 70% and 80% of vVO2 max in both shoe conditions 7 days later. RE was measured at the submaximal tests and expressed as caloric unit cost (kcal kg −1  km −1 ) and oxygen consumption (ml kg −1  km −1 ). Results: RE improved in the intervention group over time compared to the control group with small to moderate effect sizes (ES) in both shoe conditions: Effects on RE (kcal kg −1  km −1 ) in conventional running shoes: ES vVO2 70%: 0.68 (95% CI: −0.14 to 1.51), ES vVO2 80%: 0.78 (95% CI: 0–1.56). In minimalist footwear: ES vVO2 70%: 0.3 (95% CI: −0.54 to 1.14), ES vVO2 80%: 0.42 (95% CI: −0.41 to 1.25). These effects were not statistically significant (p > 0.05). The repeated-measures ANOVA also showed no group by time interactions for all submaximal RE testing conditions (p > 0.05). Conclusions: Although not reaching statistical significance, training in MFW compared to CRS resulted in small to moderate improvements in RE.